Montgomery family papers - Jackson, Maurice Elizabeth; Montgomery, Isaiah T. (Isaiah Thornton), 1847-1924.; Montgomery, Mary Virginia, 1852-; Shepperd, Gladys Byram
Typescript of a speech (1890) by Isaiah T. Montgomery; diary (1872) of Mary Virginia Montgomery, daughter of Benjamin Montgomery; biographical sketches of Mary C. Booze, daughter of Isaiah T. Montgomery, and Eugene P. Booze, her husband; typescript by Gladys Byram Shepperd entitled, The Montgomery Saga: From Slavery to Black Power (1971); thesis by Maurice Elizabeth Jackson entitled, Mound Bayou--A Study in Social Development (1937); and printed material relating to the town of Mound Bayou, Miss.
In part, typewritten transcripts.
Library of Congress Prints and Photographs Division.
Family of Benjamin Thornton Montgomery and his wife Maria, manager-slaves of Jefferson Davis and his brother Joseph Emory Davis. In 1867 the Davis's sold their plantation holdings, known as Davis Bend, to Benjamin and his two sons Thornton and Isaiah T. Montgomery. Isaiah T. Montgomery founded the African American community of Mound Bayou, Mississippi, in 1887.
Collection material in English.
Keywords: Davis, Jefferson, -- 1808-1889.; Davis, Joseph E. -- 1784-1870.; Booze, Eugene P. -- 1878-; Booze, Mary C; Montgomery family; African Americans -- Mississippi; Slavery -- Mississippi; Slaves -- Mississippi; Davis Bend (Miss.) -- History; Mississippi -- History, Local; Mound Bayou (Miss.) -- History